LAPAROSCOPIC APPENDECTOMY DURING PREGNANCY - Mishchenko, V.V.; Mishchenko, V.P.; Rudenko, I.V.; Likhachov, V.K.; Dobrovolska, L.M.; Vashchenko, V.L.; Makarov, O.G. (World of Medicine and Biology, 2021)
A laparoscopic appendectomy was performed in 73 pregnant women. The Alvarado scale was used for diagnostics. The average age of the examined was 25.7±0.5 years. 17.8 % of pregnant women were operated on in the first trimester of pregnancy, in the second ‒ 46.6 %, in the third ‒ 35.6 %. The time from the onset of the disease was 6 hours in 12.3 % of pregnant women, in 35.6 % ‒ 6‒12 hours, in 31.5 % ‒ 12‒24 hours, in 20.5 %‒ more than 24 hours. The postoperative period in all patients was uneventful. All patients were discharged for periods from 2 to 5 days after surgery. Acute appendicitis during pregnancy is a common surgical condition. Appendectomy in pregnant women should be performed even before complications from acute appendicitis and gestational complications develop. Diagnosis of acute appendicitis should be fast and accurate using additional imaging technologies. Laparoscopic appendectomy due to its advantages over open appendectomy, its safety for the health of the pregnant woman and the course of pregnancy should now become the gold standard of operations for acute appendicitis in pregnant women.
Keywords: appendicitis in pregnant women; diagnostics; tactical approaches; laparoscopic appendectomy